Smart Grid and Economic Growth: Driving Industrial Upgrading through Efficient Energy Management - Yaqian Liu (EAI Endorsed Transactions on Energy Web, 2025)
INTRODUCTION: In an era marked by rising energy demand and environmental concerns, integrating smart grid technologies is a crucial solution for promoting industrial expansion through efficient electricity control.OBJECTIVES: Here, we examine the revolutionary capabilities of smart grids to enhance economic growth by leveraging an innovative hybrid optimisation method, Trevally Optimisation (TrevOpt), at its core. The study's main focus is to show how Turnbridge's new approach can efficiently manage energy distribution and use within industrial ecosystems by leveraging TrevOpt's computational power, which combines the benefits of evolutionary algorithms and heuristics.METHODS: The heart of this paper is a discussion of how the use of smart grid technologies can catalyse industrial development. Operation eff was on another level in this experiment, enabling the optimisation of production parameters using the TrevOpt model. Integrating real-time analytics into the TrevOpt framework allows proactive management of energy resources through dynamic tuning, thereby reducing waste and enhancing system reliability.RESULTS: This highlights the potential of these technologies to inspire industrial competitiveness, drive investment in sustainability, and open new areas in energy-intensive industries to spur economic growth. The simulation presented at the end of the numerical section outlines the concrete benefits of using the TrevOpt method, including a 20% reduction in energy consumption, a 15% reduction in operational costs, and a 25% increase in overall system reliability.CONCLUSION: This study therefore provides a solid foundation that enables industries to leverage smart grid developments as a cornerstone for transforming their businesses while also protecting the environments in which people live.
Keywords: Smart Grid Technologies; Energy Management; Industrial Upgrading; Sustainability; Economic Growth; Trevally Optimizaiton (TrevOpt)